The Earth writes the Great Earthquake and the novel in post-3/11 Japan - Haga, Kōichi 1970- (Lanham Lexington Books, 2019)
"This book explores how the tremendous earthquake on March 11, 2011 impacted literary authors in Japan and generated issues and perspectives previously unrecognized in Japanese literary and social culture. The disaster itself caused an earthquake, tsunami, and an nuclear accident, and provided the grounds for "post 3/11" literature in Japan"--
Introduction: overview of post 3.11 cultural production -- Part I: The immediate impact of the 3.11 disaster on the writers' consciousness. Ecological time-space emerging from the encounter with the 3.11 -- Earthquake and tsunami: the first phase of post 3.11 literary production -- Fissures opened in literary ground: the Great East Japan earthquake and Kenzaburo Oe's in late style -- Animal agencies in post-3.11 literature -- Part II: Acceleration of the writers' ecological consciousness. Remembrance of postcolonial conditions--the earthquake's disclosure of uncommon ground: Tōhoku area as the other within -- Dystopian novels flourish in the post-3.11 period -- The emergence of a planetary sense through geographic catastrophe.
Includes bibliographical references (pages 121-124) and index.
Keywords: Fukushima Nuclear Disaster, Japan, 2011, in literature; Tohoku Earthquake and Tsunami, Japan, 2011, in literature; Japanese fiction -- Heisei period, 1989- -- History and criticism; Literature and society -- Japan -- History -- 21st century